Rescaling Sustainability Governance : Local Authorities as Pivotal Actors in Multi-Level Climate, Energy and SDG Governance - EL MAIMOUNI , Safae; ACHIBANE, Mustapha (Revue Internationale des Sciences de Gestion, 2026)
Abstract Local and regional authorities have moved to the centre of efforts to govern sustainability transitions, yet the question of how governing capacity is distributed and rescaled across levels remains under-theorised. This state-of-the-art review analyses a corpus of forty peer-reviewed articles published between 2021 and 2023 to examine how territorial governance is being rescaled around climate adaptation, energy transition and the Sustainable Development Goals (SDGs). Reading the literature through a scalar lens, the review finds that sustainability governance is converging on a multi-level architecture in which cities and municipalities act as pivotal nodes rather than autonomous units. Three patterns emerge: a horizontal integration imperative that pushes against sectoral fragmentation; an inter-municipal cooperation turn embodied in joint climate and energy plans; and a persistent capacity gap that constrains the local delivery of supranational agendas. The review also identifies recurring tensions—between vertical coherence and local autonomy, and between collaborative ambition and implementation deficits—and concludes that the field would benefit from stronger impact evaluation and more systematic North–South comparison.